Efeito da corrente de Kots em enzimas colinérgicas, purinérgicas e estresse oxidativo de mulheres sedentárias - Bona, Jordana de (2016)
The Current Kots or Russian current (RC) (2500 Hz) is a form of electrical stimulation, which causes muscle contraction. Physiotherapists use CR in Dermato-Functional area, to activate muscles or muscle groups little toned, arising from inactivity. The aim of the study was to analyze whether the application of CR alters the activity of the enzyme acetylcholinesterase (AChE), Ecto-nucleoside triphosphate diphosphohydrolase (E-NTPDase), Ecto-5'-nucleotidase, adenosine deaminase (ADA), superoxide dismutase (SOD) and catalase (CAT), as well as TBARS. The study group consisted of 15 patients of sedentary female, underwent 10 sessions of CR for 30 minutes each. He used self-adhesive electrodes placed on the rectus abdominis and the intensity (mA) was increased as tolerance of each patient. Blood was collected before and after the application of RC in sessions 1, 5 and 10. The results showed that there was an increase in the activity of AChE in acute applications 1, 5 and 10. The NTPDase showed an increase in the hydrolysis of ATP to ADP in acute applications 1 and 5. the Ecto-5'-nucleotidase enzyme showed an increase in AMP hydrolysis in acute application 1. Do not show differences in any of the applications, the activity of ADA, the activity of antioxidants SOD and CAT and levels of TBARS. Thus, the CR exerts a remarkable change in activity of enzymes that hydrolyze ACh and ATP, ADP and AMP when acutely applied. These results suggest that cholinergic and purinergic pathways are related to the beneficial effects of CR. Since the CR promotes muscle contraction and increase local blood flow.